The DNA binding domains of the yeast Gal4 and human c-Jun transcription factors interact through the zinc-finger and bZIP motifs. - Sollerbrant, K (1995)
Different Gal4 fusion proteins, expressing unrelated transcription activator domains, were found to activate transcription from promoters containing dimerized AP1 DNA binding sites. Transactivation was dependent on the first 74 amino acids of Gal4. A direct interaction between Gal4 and c-Jun was demonstrated using a GSTGal4 fusion protein and in vitro translated human c-Jun. The interaction required the zinc finger containing DNA binding domain of Gal4 and the basic-leucine zipper region of c-Jun. These results demonstrated that the specificity of Gal4 fusion proteins in transient transfection experiments in mammalian cells is not restricted to reporters containing Gal4 binding sites, but also includes promoters containing AP1 binding sites. Furthermore, the Gal4 fusion proteins also activated transcription from a pUC18 vector fragment containing several putative AP1 binding sites. Finally, our results indicate that Gal4 activator proteins binding to Gal4 binding sites and to DNA bound AP1 factors can co-operatively activate transcription.